A novel color-tunable phosphor, Na5Gd9F32:Ln3+ (Ln = Eu, Tb, Dy, Sm, Ho) sub-microcrystals: structure, luminescence and energy transfer properties. Issue 29 (11th July 2018) - Yang, Junfeng; Dong, Jianchao; Wu, Ruiyang; Wu, Hongyue; Song, Hongbo; Gan, Shucai; Zou, Lianchun
Abstract : Ln 3+ -Doped fluorides are economical and highly efficient luminescent materials, which play a crucial role in LEDs, biolabeling, and sensors. Abstract : Ln 3+ -Doped fluorides are economical and highly efficient luminescent materials, which play a crucial role in LEDs, biolabeling, and sensors. Therefore, Na5 Gd9 F32 :Ln 3+ sub-microspheres with tunable multicolor emissions were successfully synthesized via a simple water bath method employing colloidal Gd(OH)CO3 spheres as precursors. Samples were characterized by XRD, SEM, TEM, EDS and PL. It was found that the hydrolysis of BF4 − ions had a dynamic effect on the retention of the morphology of the product owing to the mild reaction environment caused by the low hydrolysis rate of BF4 − ions. Upon excitation by ultraviolet light, the Na5 Gd9 F32 :Ln 3+ (Ln = Eu, Tb, Dy, Sm, Ho) phosphors underwent characteristic f–f transitions and gave rise to red, green, green, yellow, and pale green emissions, respectively. Moreover, various emission colors could be obtained by using different excitation wavelengths and adjusting the Eu 3+ /Tb 3+ molar ratio owing to energy transfer between Tb 3+ and Eu 3+ ions in the Na5 Gd9 F32 host. The energy transfer mechanism was demonstrated to be a dipole–dipole interaction. The multicolor luminescent phosphors with a certain dopant concentration based on a single host and excitation wavelength may have potential applications in the field of lighting displays.